Implementasi Media Edmodo Dalam Mata Kuliah Bahasa Arab Di Iai Nazhatut Thullab Sampang - Moh. Hasyim Asy’ari (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
This research is entitled "the implementation of Edmodo media in Arabic language courses at IAI Nazhatut Thullab Sampang. And the purpose of this study is to describe: 1)process of learning Arabic courses with Edmodo media at IAI Nazhatut Thullab Sampang, 2)constraints on applying Edmodo media in learning Arabic courses at IAI Nazhatut Thullab Sampang. In this study, researchers used a qualitative research methodology, while the location of this study was in the campus of IAI Nazhatut Thullab Sampang, in this study the researchers obtained data from the study program, semester 1 students of MPI study program, Arabic language lecturers, and observational data that would be carried out by researchers, as well as the written data that researchers need. Researchers use data collection procedures, data analysis, and checking validity. The results of this study are: 1) Arabic language lecturers submit lecture contracts to be worked on for one semester. Then the Arabic language lecturer explained about Edmodo media to students, the Arabic language instructor told students to create an Edmodo account using a Gmail account. and with the various features in Edmodo Arabic language lecturers can provide exercises such as sending Arabic language videos to improve their specific language and student experience, it makes it easier for students to learn Arabic. 2)in the use of edmodo media when the network is not good because some students in their homes in the countryside, accompanied by students' lack of understanding of the use of edmodo such as functions rather than features contained in edmodo, thus hampering the process of learning Arabic.